Psychological and social consequences of deafblindness for siblings: a systematic literature review - Arcous, Marine; Potier, Rémy; Dumet, Nathalie (Frontiers in Psychology, 2024)
The onset of deafblindness profoundly impacts both the individual with this condition and the individual’s family, including siblings. While current studies have primarily focused on the impact felt by parents or spouses, the distinct experiences of siblings have received comparatively less attention. This systematic review addresses the existing research gap regarding the psychological and social consequences experienced by siblings of individuals with deafblindness. A comprehensive search was conducted across multiple electronic databases, including PsycINFO, PsycARTICLES, Dissertations & Theses (on ProQuest), ERIC (Education Resources Information Center), International Bibliography of the Social Sciences (IBSS), Sociological Abstracts, Google Scholar, PubMed, and Cairn Info. Seven studies were identified as meeting the eligibility criteria for inclusion. The review revealed that siblings of individuals with deafblindness face psychological and social challenges, including emotions such as feelings of neglect, resentment, embarrassment, jealousy, and anxiety. Siblings also grapple with communication difficulties, contributing to feelings of exclusion and insecurity. In addition, these siblings take on significant responsibilities within the family and encounter obstacles in forming relationships outside the family. These findings underscore the need of interventions to improve the well-being of siblings of individuals with deafblindness by addressing their psycho-emotional needs and promoting positive social interactions. These findings align with studies conducted on siblings of children with other disabilities. However, additional research is crucial to investigate overlooked dimensions, particularly positive factors like coping mechanisms and resilience, that may influence the mental health and social experiences of these siblings.